Numerical Simulation of Nanosilica Sol Grouting for Deep Tunnels Based on the Multifield Coupling Mechanism - Dongjiang Pan; Kairong Hong; Helin Fu; Zhiguo Li; Limeng Zhang; Gaoming Lu; Feixiang Sun; Shiyu Wen (Geofluids)
Grouting is an effective technical way for the construction of deep tunnels in unfavorable geological conditions. The fluid-solid-chemical coupling mechanism of grouting process is analyzed from the following three aspects: influence of physical properties of silica sol on permeability coefficient, dynamic changes of porosity and permeability of geotechnical media with seepage pressure, and governing equations for flow and mass transfer characteristics. A dynamically changing model for nanosilica sol grouting in deep tunnels is established, considering the changing physical properties of grout and surrounding rock. Based on the Xianglushan Tunnel of Yunnan Water Diversion Project, the temporal and spatial evolution of silica sol grout is studied. The effect characteristics of grouting pressure and initial permeability are clarified. The rationality of this model is verified by classical Newtonian fluid grouting theory. The main conclusions: with the molar concentration as the index, the grout range can be divided into the raw grout region and the transition region; with the decrease of the grouting pressure, the growth rate of the normal grouting radius and the axial grouting radius will gradually decrease; due to the mechanical dispersion and molecular diffusion, the range of the transition region will gradually increase with time. The ratio of the transition region to grouting radius fluctuates slightly with time under the initial permeability of 5 D. The fluctuation increases with the decrease of initial permeability, and the average ratio increases with the decrease of grouting pressure. This study can provide theoretical guidance for grouting design of deep tunnel engineering.